Analysis of Risk Factors for Pulmonary Tuberculosis Incidence - Nevi Hasnita; Fachmi Ichwansyah; Faisal bin Abdurrahman; Said Usman; Meutia Zahara (Indonesian Journal of Global Health Research, 2025)
Pulmonary tuberculosis (TB) cases in Nagan Raya have increased every year. Efforts to prevent tuberculosis transmission with healthy lifestyle behaviors have been carried out. However, the prevalence of pulmonary tuberculosis is still high and many factors are associated with the incidence of pulmonary tuberculosis—analytical study with a case-control approach to determine risk factors for tuberculosis in the Nagan Raya district. The sample in this study was 290 people consisting of 58 cases and 232 controls. The sampling technique used purposive sampling. Data was collected by interviewing respondents, observing, and reporting TB case records. Multivariate analysis using multiple logistic regression tests with a 95% confidence level. The results showed that the characteristic factors associated with the incidence of pulmonary TB were primary education (p=0.002), not working (p=0.000), and income <REGIONAL MINIMUM WAGE (p=0.001). Environmental factors associated with the incidence of pulmonary TB were the number of household members >4 people (p=0.036) and no ventilation in each room (p=0.000). Health factors associated with the incidence of pulmonary TB were underweight nutritional status (p=0.019), obese nutritional status (p=0.042), and not containing BCG (p=0.014). The most dominant factor associated with the incidence of pulmonary TB is not working (OR = 4.17; 95% CI = 1.36-12.73). Respondents who did not work had a 4.17 times higher risk of experiencing pulmonary TB than those who did not work after controlling for environmental and health factors. For this reason, it is expected that respondents need to increase their income to prevent transmission of pulmonary TB and maintain cleanliness, improve nutritional status and limit contact with TB sufferers